Interactions between Health and Labour Market Outcomes over the Life Course - Flavel, Joanne (My University, 2015)
The project applies an economic framework to empirically analyse relationships between poor health and labour market outcomes in Australia. By discovering the ways in which poor health during working age can result in accumulating labour market disadvantage over the life course, this project will enable a better understanding of the effect of earlier health inequities on outcomes post retirement, particularly in relation to the degree of income and health inequities for retirees. It will build on previous research which studied the relationship between health and a number of individual labour market outcomes by conducting a thorough analysis of the extent to which poor health results in accumulating disadvantage across a range of outcomes. It is proposed that the effects of ill health on the earnings distribution and on labour force experience leads to increased income and health inequities post retirement.
Keywords: Health; Employment -- Labour Markets; Health and wellbeing; Labour market; Health; Employment; Labour Markets; Health and wellbeing; Employment and unemployment